Pengembangan panduan permainan tradisional bugis-makassar dalam meningkatkan keterampilan sosial siswa - Oktaviana Kasim, Sinta Nurul (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
The problems which was described in this study can be divided into two parts (1) How to develop the guidance of Bugis-Makassar Traditional Games as acceptable counseling guidance media based on the usefulness, accuracy, and relevancy in increasing social skill of students. (2) How to implement the guidance of Bugis-Makassar traditional games as counseling guidance media. The purposes of this study are (1) to develop the guidance of Bugis-Makassar Traditional Games as acceptable counseling guidance media based on the usefulness, accuracy, and relevancy in increasing social skill of students. (2) to know the implementation of Bugis-Makassar traditional games guidance as counseling guidance media. This study used development model developed by Borg and Gall which examines the development of this Bugis-Makassar traditional games media. Participants of this study in this small trial consist of 12 students. Data collection technique was questionnaire and interview. The results showed that (1) Bugis-Makassar traditional games guidance can be accepted based on the usefulness, accuracy, and relevancy in increasing social skill of students. (2) the guidance of Bugis-Makassar traditional games as counseling guidance media can be implemented properly in SMPN 8 Makassar.